A BOOK REVIEW: THEORY AND PRACTICE OF ENGLISH LANGUAGE TEACHING IN INDONESIAN CONTEXT - Shirly Rizki Kusumanigrum (Soegijapranata Catholic University, 2011)
Few days before I had my thesis examination, I met my Professor. He offered me to type some manuscripts to be published in a book. With pleasure, I accepted his offer. By the time I read the manuscripts, I got lots of information about English Language Teaching in Indonesia. Finally, the time comes; and the manuscripts are compiled into a book entitled